Preliminary Assessment for Heavy Metal Removal from Synthetic Water Matrix Using an Organic/Inorganic Composite - Roxana Ioana Matei (Brazdis); Anda Maria Baroi; Radu Claudiu Fierascu; Toma Fistos; Irina Elena Chican; Georgeta Ivan; Ioana Silvia Hosu; Cristian Andi Nicolae; Irina Fierascu (Proceedings, 2023)
Pointed and diffused discharges of various compounds in the various compartments of the environment can end up disturbing ecosystems through rivers, lakes, groundwater and oceans, thus leading to a strong imbalance. The present paper describes a new and innovative composite material, based on organic and inorganic phases (pectin and hydroxyapatite), used as an adsorbent of heavy metals (Cd and Pb) from waters.